2022
DOI: 10.4103/sjg.sjg_624_21
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the EVendo score for the prediction of varices in cirrhotic patients

Abstract: Background: Screening endoscopy for varices may be deferred when the calculated EVendo score is ≤3.90. This novel score has not been validated in an external cohort. This study aimed to assess the performance of the EVendo score and compare it with the Baveno VI criteria. Methods: We identified and calculated this score in all cirrhotic patients who underwent screening endoscopy for the first time with laboratory tests and liver stiffness measurements within 6 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…This is the case for a novel score called EVendo, which considers several factors: the presence of clinical ascites, hemoglobin (g/dL), platelet count (count/1000), AST (U/L), and blood urea nitrogen (BUN) (mg/dL). EVendo score demonstrated its safety in clinical practice for predicting esophageal varices and varices needing treatment, with a higher number of spared endoscopies than with Baveno VI [ 50 , 51 ].…”
Section: Reviewmentioning
confidence: 99%
“…This is the case for a novel score called EVendo, which considers several factors: the presence of clinical ascites, hemoglobin (g/dL), platelet count (count/1000), AST (U/L), and blood urea nitrogen (BUN) (mg/dL). EVendo score demonstrated its safety in clinical practice for predicting esophageal varices and varices needing treatment, with a higher number of spared endoscopies than with Baveno VI [ 50 , 51 ].…”
Section: Reviewmentioning
confidence: 99%
“…5,[64][65][66] Studies have shown that patients most likely to have high-risk varices are those with decompensated cirrhosis, a platelet count ≤150x10 3 /mm 3 , and liver stiffness ≥20 kPa (determined by transient elastography). 65,67,68 Consequently, most of the experts (>75%) recommended upper gastrointestinal endoscopy within 6 months from study entry to assess the risk of hemorrhage from varices in all patients with HCC prior to initiation of atezolizumab plus bevacizumab therapy in line with published guidelines (Figure 5C). Additionally, atezolizumab could be immunogenic and induce undesirable anti-drug antibody (ADA) responses.…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…It also revealed a high negative predictive value of 96% in ruling out varices that required treatment. Similarly, Alswat K et al [12] validated EVendo score in an arab population and proposed a higher cutoff of < 4.5 in ruling out the patients with varices requiring treatment with a sensitivity of 83%.However, it lacked specificity.…”
Section: Introductionmentioning
confidence: 99%